Inelastic response spectrum Early history. - Riddell, Rafael (Earthquake engineering & structural dynamics.)
Detailing the time period from, roughly, 1950 through 1980, this Historical Note documents the development of the initial concept of the inelastic response spectrum and how it evolved to become the basis for rational procedures for earthquake-resistant design, which are used even today.